2001
DOI: 10.1007/bf02234388
|View full text |Cite
|
Sign up to set email alerts
|

Colonic J-pouch function in rectal cancer patients

Abstract: Both preoperative and postoperative chemoradiation therapy adversely affects continence and evacuation in patients with colonic J-pouch. Because radiation-induced damage to the normal tissues is known to be cumulative over time, long-term progressive dysfunction of the anal sphincter and neorectum are causes of concern. Consideration should be given to excluding the anal canal from the field of irradiation in patients with Stage II and III rectal cancer, whenever a sphincter-preserving procedure is planned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 30 publications
3
24
0
2
Order By: Relevance
“…These results are in accordance with other reports in the literature [27][28][29]. In addition to the limited number of patients studied, the timing of postoperative measurements is a limiting factor in these studies and may explain discrepancy among authors [30][31][32][33][34][35]. With recent ongoing advances in neoadjuvant therapy regimes, a tendency to more favorable postoperative functional results can be expected, however results are still conflicting as seen in Table 10.1 [36][37][38][39][40].…”
Section: Effects Of Surgerysupporting
confidence: 93%
See 1 more Smart Citation
“…These results are in accordance with other reports in the literature [27][28][29]. In addition to the limited number of patients studied, the timing of postoperative measurements is a limiting factor in these studies and may explain discrepancy among authors [30][31][32][33][34][35]. With recent ongoing advances in neoadjuvant therapy regimes, a tendency to more favorable postoperative functional results can be expected, however results are still conflicting as seen in Table 10.1 [36][37][38][39][40].…”
Section: Effects Of Surgerysupporting
confidence: 93%
“…15). [27] 1994 Conventional 10 No 3 years Yes Gervaz et al [31] 2001 Conventional 45 Yes 2 years No Denhi et al [36] 2002 Conventional 28 Yes (Partially) 1 year No Nathanson et al [28] 2003 Conventional 109 No 5 years No Ammann et al [25] 2003 Conventional 28 Yes 1 year Yes Saito et al [29] 2004 Conventional 20 No 1 year Yes Pietsch et al [26] 2007 Conventional 12 No 6 months Yes Coco et al [37] 2007 Conventional 100 Yes 1 year No Canda et al [38] 2010 Conventional 31 Yes 1 year Yes Denost et al [39] 2011 Conventional 51 Yes 5 years No…”
Section: Management Of Radiation-related Functional Problemsmentioning
confidence: 98%
“…This scoring system, which has been used by several investigators, was designed to quantify overall functional results and is calculated by the simple addition of all arbitrary scores. 26,[52][53][54][55] The distance from the anal verge to the anastomosis in colonic J-pouch reconstruction has been reported to range from 1 to 8 cm, 7,[9][10][11]19,21,23 although the ideal anastomotic location for colonic J-pouch reconstruction has not been established. In a previous study, we tried to determine the level at which J-pouch reconstruction provides a functional advantage over straight anastomosis and found that colonic J-pouch reconstruction is indicated when the anastomosis is less than 8 cm from the anal verge, and is essential when it is less than 4 cm from the anal verge.…”
Section: Discussionmentioning
confidence: 99%
“…Gervaz et al 37 investigated the impact of adjuvant chemoradiotherapy on DF in patients undergoing J-pouch reconstruction. In their study, incontinence to gas, liquid stool, and solid stool were significantly more frequent in the irradiated group.…”
Section: Defecation Function (Df)mentioning
confidence: 99%